Essential surgery: key messages from Disease Control Priorities, 3rd edition. Issue 9983 (30th May 2015) - Mock, Charles N; Donkor, Peter; Gawande, Atul; Jamison, Dean T; Kruk, Margaret E; Debas, Haile T; ,
Summary: The World Bank will publish the nine volumes of Disease Control Priorities, 3rd edition, in 2015–16. Volume 1— Essential Surgery —identifies 44 surgical procedures as essential on the basis that they address substantial needs, are cost effective, and are feasible to implement. This report summarises and critically assesses the volume's five key findings. First, provision of essential surgical procedures would avert about 1·5 million deaths a year, or 6–7% of all avertable deaths in low-income and middle-income countries. Second, essential surgical procedures rank among the most cost effective of all health interventions. The surgical platform of the first-level hospital delivers 28 of the 44 essential procedures, making investment in this platform also highly cost effective. Third, measures to expand access to surgery, such as task sharing, have been shown to be safe and effective while countries make long-term investments in building surgical and anaesthesia workforces. Because emergency procedures constitute 23 of the 28 procedures provided at first-level hospitals, expansion of access requires that such facilities be widely geographically diffused. Fourth, substantial disparities remain in the safety of surgical care, driven by high perioperative mortality rates including anaesthesia-related deaths in low-income and middle-income countries. Feasible measures, such as WHO's Surgical Safety Checklist, have led to improvements in safety and quality. Fifth, the large burden of surgical disorders, cost-effectiveness of essential surgery, and strong public demand for surgical services suggest that universal coverage of essential surgery should be financed early on the path to universal health coverage. We point to estimates that full coverage of the component of universal coverage of essential surgery applicable to first-level hospitals would require just over US$3 billion annually of additional spending and yield a benefit–cost ratio of more than 10:1. It would efficiently and equitably provide health benefits, financial protection, and contributions to stronger health systems.